Ukrainian peasantbreadwinner: historical and ethymological discourse - Markova, Svitlana; Sheremeta, Liliya (Ukrainian Peasant, 2021)
Introduction. The article analyzes the changing attitude to the Ukrainian peasants-landowners in the Soviet society; compares the etymology of the Ukrainian word «selo» and Russian «derevnya»; traces the dynamics of defi nitions: «peasant», «master», «goodman» «owner», «individual», «privateer», «farmer», «kurkul» (in the Russian Empire; the Ukrainian People’s Republic; the Soviet Union / the Ukrainian SSR) identifi ed the most commonly used Soviet labels of Ukrainian peasantsproprietors: «kurkuls», «kulaks», «bandits», «petlyurovtsy», «former people» (both peasants and intellectuals were called so), «petty bourgeois», etc. The Soviets labeled the children of the «kulaks» as «kurkul’s bastards», «kurkul snouts», «kurkul henchmen»; It is traced how the meaning of the word «kurkul» changed in the Ukrainian language during the Soviet period. The aim is to analyze the etymology of the words “village”(“selo”) and “peasant” in the context of civilizational development of Ukraine; to trace the acquisition of the negative content of the phrases “Ukrainian peasant” (Ukrainian farmer), peasant-proprietor, tiller in the Russian Empire and the Soviet Union /the Ukrainian SSR. The methodology of the research is based on the principles of historicism; civilizational, interdisciplinary approaches; and the concepts of W. Noll and E. Durkheim. The authors used the method of critical analysis of sources, typological, as well as analysis, synthesis, generalization. Scientifi c novelty. For the fi rst time the article made an attempt to synthesize linguistic and historical knowledge in order to trace the changes in the stylistic coloring of the words «village», «Ukrainian peasant» (Ukrainian farmer), peasantproprietor (master) in the Soviet society. Conclusions. Ukrainians were representatives of an agrarian civilization with thousands of years of history and culture. The word «village» has a long etymology and kinship with Slavic languages. It comes from the Proto-Slavic language. The Ukrainian peasantry has traditionally sought economic freedom and aspired to self-governing forms of government and economic management. Historically Ukrainians were called ploughmen, breadwinners, tillers, farmers, land guardians and so on. From the end of the 19th to the beginning of the 20th centuries, Ukrainians in the Russian Empire were disparagingly called «muzhik nation», «hillbilly», «khokhly». The legitimization of the Communist regime in Ukraine, the rise of the lumpen proletariat, the creation of a «new man», the «Soviet people» a priori did not presuppose respect for the farmer, the existence of private property, or traditional Ukrainian culture. And while in the Ukrainian People’s Republic the peasant proprietors were treated as «masters», «goodmen», «individuals», «privateers» and «farmers», the Bolshevik leaders viewed them through the prism of inferiority. The successful (wealthy) Ukrainian peasants-proprietors after the Bolshevik occupation of the UPR were labeled «kurkuls», «kulaks», «bandits», «petlyurovtsy», «former people», «petty bourgeois», «rednecks»; the children of «kurkuls» were called «kurkul bastards», «kulak snouts», «kulak henchmen». The Soviets labeled, branded the entire «kurkul’s» family. The village and Ukrainian peasants were treated as something secondary, serviceable, backward, «muzhychy»; they were disparagingly called «redneck», «byky», «derevnya».